2016
DOI: 10.2355/isijinternational.isijint-2015-288
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Test Conditions on Corrosion Reactions and Hydrogen Absorption in Hydrogen Embrittlement Tests Using an Ammonium Thiocyanate Solution

Abstract: Ammonium thiocyanate is widely used as a reagent for promoting hydrogen absorption by high-strength steels. The effects of the solution concentration, temperature and dissolved oxygen on corrosion film formation, corrosion reactions and hydrogen absorption were investigated in a hydrogen embrittlement test environment using an ammonium thiocyanate aqueous solution. A still bath of a 20 mass% ammonium thiocyanate solution displayed a supply limitation, whereas a solution with flow influenced the corrosion and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…The efficiency of this solution in the H permeation was reported several times in the literature [19,[21][22][23][24][25][26][27][28][29]. Ammonium thiocyanate (NH 4 SCN) is widely used as a reagent (hydrogen recombination poison) for promoting hydrogen absorption by steels, and during hydrogen charging, the solution was de-aerated with N 2 [22,30]. Samples were connected to a cathode, and a Pt coil was connected to the anode.…”
Section: Methodsmentioning
confidence: 96%
“…The efficiency of this solution in the H permeation was reported several times in the literature [19,[21][22][23][24][25][26][27][28][29]. Ammonium thiocyanate (NH 4 SCN) is widely used as a reagent (hydrogen recombination poison) for promoting hydrogen absorption by steels, and during hydrogen charging, the solution was de-aerated with N 2 [22,30]. Samples were connected to a cathode, and a Pt coil was connected to the anode.…”
Section: Methodsmentioning
confidence: 96%
“…During plant tests, the hydrogen charging of car parts was carried out in an electrochemical cell with impressed cathodic protection current. A plexiglass tank, large enough to contain a sufficient portion of the test pieces, constituted the electrochemical cell and was filled with a solution of distilled water with NaCl (3.5% w/w) and ammonium thiocyanate (0.35% w/w) . The anode was a large grid in AISI 316L and the charging current density was kept between 5 and 10 A m −2 .…”
Section: Experimental Methodsmentioning
confidence: 99%
“…7, NH 4 SCN decreased the cathodic current, and the Tafel slopes of cathodic reaction were about − 0.120 V•decade − 1 in acidic condition of pH 3.0. Therefore, it was considered that the dominant cathodic reaction in this study was hydrogen evolution reaction, not reduction of SCN − in Ichiba's 5) study. To determine the mechanism of HER, the Tafel slope or the dependence of surface hydrogen concentration on hydrogen charging current should be obtained.…”
Section: Estimation Of Hydrogen Evolution Reactionmentioning
confidence: 96%
“…A number of studies about the effects of SCN − on hydrogen entry and corrosion behavior have been reported so far. Ichiba et al 5) measured the corrosion rate and the polarization curves of steel bars for prestressed concrete in 0-20 mass% NH 4 The effect that SCN − accelerate hydrogen entry into steel is widely known. Marshakov et al 6) pointed out that SCN − increased hydrogen entry efficiency by using Iyer Pickering Zamanzadeh (IPZ) analysis.…”
Section: Effect Of Ammonium Thiocyanate On Hydrogen Entry Behavior Of Low Alloy Steel Under Galvanostatic Cathode Chargingmentioning
confidence: 99%